Integration of activation maps of epicardial veins in computational cardiac electrophysiology. (December 2020) - Stella, Simone; Vergara, Christian; Maines, Massimiliano; Catanzariti, Domenico; Africa, Pasquale Claudio; Demattè, Cristina; Centonze, Maurizio; Nobile, Fabio; Del Greco, Maurizio; Quarteroni, Alfio
Abstract: In this work we address the issue of validating the monodomain equation used in combination with the Bueno-Orovio ionic model for the prediction of the activation times in cardiac electro-physiology of the left ventricle. To this aim, we consider four patients who suffered from Left Bundle Branch Block (LBBB). We use activation maps performed at the septum as input data for the model and maps at the epicardial veins for the validation. In particular, a first set (half) of the latter are used to estimate the conductivities of the patient and a second set (the remaining half) to compute the errors of the numerical simulations. We find an excellent agreement between measures and numerical results. Our validated computational tool could be used to accurately predict activation times at the epicardial veins with a short mapping, i.e. by using only a part (the most proximal) of the standard acquisition points, thus reducing the invasive procedure and exposure to radiation. Highlights: Cross-validation of the monodomain model for cardiac electro-physiology. Use of patient-specific epicardial activation measures and left ventricle geometries. Accuracy independent of fibers orientation and number of measures. Prediction of the latest activation time in the epicardial veins, for the Cardiac Resynchronization Therapy.